An Ordinance Relating to Misdemeanors, § 21, in The Act of Incorporation and Ordinances of the City of Bunker Hill, Illinois 66 (1873). - (:unkn) unknown (My University, 1873)
Whoever shall, in any part of the city, fire or discharge any cannon, gun, pistol or other firearms, or shall set off, fire or explode any torpedo, fire cracker, fire ball, rocket or other fire works, whatever, or shall make or kindle any bonfire shall forfeit and pay the sum of not less than one dollar for each offense
Keywords: DISCHARGE